Teacher's effectiveness of teacher-student interpersonal relationship at International Islamic School, Gombak. - Yusuf, Hajar Mojirayo (Institute of Education, International Islamic University Malaysia, 2011)
This study examines students' perceptions of their teacher-student interpersonal relationships with the International Islamic School Malaysia (IIS) as the case study. This research adopts a mixed methodology strategy and data were collected through surveys and interview. The Questionnaire on Teacher Interaction (QTI) adapted from Wubbels (1995), was utilized to carry out this research. Using a convenient sampling procedure, a survey has been conducted on 141 samples (121 students and 20 teachers). The researcher used descriptive statistics, ANOVA and multiple regression analysis to interpret the data. The results suggest that teachers and students have different perceptions of teacher-student interpersonal relationships. It also shows that, nationality has no effect on teachers and students' perceptions towards teacher-student interpersonal relationship. It also reveals that there is no statistical difference between male and female perception towards teacher-student interpersonal relationship. It is hoped that findings of this research will provide policy makers and education administrators with necessary information in their efforts to enhance teacher effectiveness.